Peroxidase as the Major Protein Constituent in Areca Nut and Identification of Its Natural Substrates. (24th October 2013) - Liu, Yu-Ching; Chen, Chao-Jung; Lee, Miau-Rong; Li, Mi; Hsieh, Wen-Tsong; Chung, Jing-Gung; Ho, Heng-Chien
Abstract : Numerous reports illustrate the diverse effects of chewing the areca nut, most of which are harmful and have been shown to be associated with oral cancer. Nearly all of the studies are focused on the extract and/or low molecular weight ingredients in the areca nut. The purpose of this report is to identify the major protein component in the areca nut. After ammonium sulfate fractionation, the concentrated areca nut extract is subjected to DEAE-cellulose chromatography. A colored protein is eluted at low NaCl concentration and the apparently homogeneous eluent represents the major protein component compared to the areca nut extract. The colored protein shares partial sequence identity with the royal palm tree peroxidase and its peroxidase activity is confirmed using an established assay. In the study, the natural substrates of areca nut peroxidase are identified as catechin, epicatechin, and procyanidin B1. The two former substrates are similarly oxidized to form a 576 Da product with concomitant removal of four hydrogen atoms. Interestingly, oxidation of procyanidin B1 occurs only in the presence of catechin or epicatechin and an additional product with an 864 Da molecular mass. In addition, procyanidin B1 is identified as a peroxidase substrate for the first time.